1996
DOI: 10.1136/bmj.312.7045.1516
|View full text |Cite
|
Sign up to set email alerts
|

Audit study of next of kin's satisfaction with clinical necropsy service

Abstract: The public may have considerable appreciation of the nature and purposes of necropsy,' but these attitudes could change when people are faced with requests for necropsies on members of their own family. We investigated the level of satisfaction of bereaved relatives with a clinical necropsy service. Subjects, methods, and resultsWe selected 206 consecutive requests for clinical necropsies for inclusion in our study. At least six months (range 6-14 months) after the requests had been made, a specially trained a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 2 publications
1
18
0
Order By: Relevance
“…This finding is similar to a previous study which showed that very few GPs either knew or had requested a non-coronial postmortem examination 2. Another factor for not requesting a non-coroner (clinical) autopsy is that a high number of relatives are distressed by requests for an autopsy,1 a view that is shared by GPs.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This finding is similar to a previous study which showed that very few GPs either knew or had requested a non-coronial postmortem examination 2. Another factor for not requesting a non-coroner (clinical) autopsy is that a high number of relatives are distressed by requests for an autopsy,1 a view that is shared by GPs.…”
Section: Discussionsupporting
confidence: 88%
“…However, an increase in rate is unlikely unless the public and primary and secondary care clinicians are made aware of the value of autopsies. Some have suggested that training should be provided for all grades of doctors in communication skills for dealing with death and dying 1. Better communication between GPs, hospital clinicians, pathologists, and coroners may also increase the rate of autopsies.…”
Section: Discussionmentioning
confidence: 99%
“…Others have shown that families can experience distress if communication is poor 5 or may be less likely to agree to a PM if an approach is perceived as insensitive. 6 Two important obstacles that also emergedthat is, devaluation of PMs among younger staff, and the feeling that PMs may be unnecessary in certain cases (known cause of death, prematurity)-have also been highlighted in the wider literature.…”
mentioning
confidence: 99%
“…Even though the distress of relatives is likely to make the request difficult, there is some evidence that this task is often delegated to junior staff 589 who are offered little training. 590 Such practices not only undervalue the traumatic impact of this work on junior staff, but are a failed opportunity for preventing psychological distress among the patient's family and among staff.…”
Section: Request For An Autopsymentioning
confidence: 99%